Produção textual e conhecimentos prévios do professor - Arruda, Miriam da Silva (2009)
Registered in this dissertation studies were developed in the programme of postgraduate studies in the Portuguese language and its theoretical PUCSP is anchoring the assumptions of linguistic textual strand guided socio-cognitive-, on an interface with those developed by Lexicology.The theme developed are textual production processes-discursive written language-in this case, Portuguese, idiomizada and conceived as a communicative not tense, standard by Marcos sociocultural history of the Brazilian people-study and learning object proficiency whereby teachers must meet in this discipline, or middle school. The purpose-to contribute to school institutions may cooperate with the movements of Brazilian society recontextualização by critical review discursive practices, including those pertaining to the teacher's teaching practices of mother tongue, to be reinterpreted by contemporary linguistic parameters ranging research into the field of education linguistic. The problem limited to the results of evaluation diagnosis concerning education proficiency written production practices that are registered in the SARESP, was considered in relation to own knowledge of the object browser in its role as a teacher, whose area of such practices were not part of the curriculum of its vocational training. You can say that this goal was achieved, insofar as it could be measured by the following specific objectives: (a) organize theoretical underpinnings capable of providing an understanding of principles concerning linguistic textual-enabled browser to understand the assumptions relating to: 1) text inseparable from design conception of speech: the methodological procedures; 2) accounted for him to situate the language elements such as patida point for the treatment inensivo reading practices; a. 3) operate with the principle of Intertextuality to extend its own previous knowledge; b) recognise writer proficiency skills through the use of grammatical lexicon-strategies in written record of the text-product, as well as those that answer by the need to learn to talk with the author-producer; c) identify text produced by secondary written production skills which have not yet been developed during the process of their escolarizações-the same procedures methodological employees to discover the writer/producer strategies proficiency, guided reading the treatment of texts produced by students-writers who underwent the assessment of Saresp. Comparing the data of the results obtained in chapter II and those that could last chapter, considers that the skill set developed by students-not writers was essentially those tabling incomprehensible to the browser itself, in a time leading up to this survey